Influencia del co-sustrato y soporte de inmovilización en la velocidad de reducción de la acetofenona empleando monascus kaoliang como biocatalizador. - Linares Valdivia, María Del Pilar (2012)
This research has aimed to develop a method of immobilizing cells to allow regeneration of the coenzyme (NADH) with a suitable co-substrate to carry out the reduction of Acetophenone with good yields. To this solid growth through three Ascomycetes (filamentous fungi) Gongronella butleri, Diplogelasinospora grovesii and Monascus kaoliang determined, being the latter which grew more biomass production. Monascus kaoliang was employed as a biocatalyst for testing immobilization with the Union method supports by Adsorption, with the intention of finding better derivative immobilized, productivity, performance, maximum conversion, conversion, initial velocity was evaluated. For coenzyme regeneration was tested with two co-substrates glucose and isopropanol. The results obtained in the laboratory can determine that derivatives immobilized in polyurethane foams using glucose as co-substrate are good support to carry out the reduction process acetophenone since given its high porosity cells are exposed to the reaction medium without problems diffusional within the matrix. In this regard, the bioreducciones are a useful tool in the synthesis of pharmaceuticals and fine chemicals. Furthermore, only a small number of fungi have been described as good producers reductases.